Exploring the use of technology in coaching education: Digital coach development or disaster? - McCarthy, L.; Hounsell, T. (Olympic & Paralympic Coach, 2019)
In 2016, Sport England (the lead government agency for sport, in England) established a four-year vision for sports coaching. The purpose of the Coaching Plan for England (Sport England, 2016) was to establish an agenda that would ultimately achieve the goal of enhancing the experiences of sports participants, underpinned by more strategic approaches to effective coach development. It was suggested that one of three key enablers in this process would be the use of technology; specifically, how technology might play a role in the learning and development of sport coaches. As a result, organisations charged with the delivery of coach education (e.g., National Governing Bodies, Higher Education Institutions, etc.) have sought to embrace technology, embedding it into coach education programmes wherever possible. While this might seem quite a localised concern, technology is being embedded in coach education programmes the world over, as a remedy to a variety of issues. Firstly, technology has the capacity to manage the growing scale and widening the scope of coach education. There is growing impor-tance attached to coach education and as a result, provision is being offered by a wide variety of organisations. For example, according to Gano-Overway & Diffenbach (2019), 308 higher educa-tion providers in the United States are offering coach education programmes currently. The broader point is also corroborated in the work of McCarthy and Stoszkowski (2018, p317), who claim, "... coach education and development programmes, once the exclusive domain of national governing bodies (NGBs), are now increasingly being offered by disparate organisations including; charities (e.g., Street Games), local authorities, private enterprises, and further education colleges (FE) (Lara-Bercial, et al., 2016)". Coach education programmes delivered online can be wide-reaching (scale) and engage with otherwise isolated coaches (scope). Secondly, technology-enhanced coach education can form a more consistent offer, reducing the void between programmes where coaches might otherwise become detached from coach learning. This seems important since Sport England (2016) argue that a barrier to increasing the diversity of the coaching family is a lack of consistent opportunities. Examples are beginning to emerge where tech-nology such as Hive Learning (https://www.hivelearning.com/site/) and Coach Logic (https://www. coach-logic.com/) are being used by NGBs to `smooth out the journey` for coaches, on their coach education pathway; ultimately encouraging more frequent and consistent engagement. Thirdly, and importantly, technology-enhanced coach education programmes have the potential to ad-dress the criticism leveled at coach education (as organised typically), that it is rarely considered im-portant, impactful or useful by coaches (Piggott, 2012). In fact, coaches report that they have a desire to (or currently do), engage with technology as part of their ongoing development anyway (Nelson, Cushion and Potrac, 2012). Technology-enhanced coach education programmes have the capacity to provide a more authentic and contextualised experience (i.e. are about me and my athletes, where I can video capture my coaching in my unique context) to provide an experience which represents a shift from coach education programmes being about the provision of `gold standard` recipes (Abra-ham and Collins, 1998).